Efektivitas Pelaksanaan Kerja Hubungan Industrial di PT. Interline Indonesia - Resya Dwi Marselina; Nurleni Nurleni; Devi Agrianti; Vinni Imania; Hilma Sadatil Alawiyah; Mohammad Zein Alfiansyah; Ilham Fadillah Pramana (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This article explores the effectiveness of industrial relations work implementation at PT. Interline Indonesia. The study aims to investigate and analyze the extent to which the implementation of industrial relations work in the company can contribute to efficiency, productivity, and welfare. Through literature review, research findings, and discussion, factors influencing industrial relations, the role of management in improving effectiveness, and recommendations for improving harmonious industrial relations in the company have been examined. The study found that effective industrial relations work implementation can lead to improved efficiency, productivity, and welfare in the company. The article concludes with recommendations for companies to improve their industrial relations work implementation to achieve better outcomes.